Kondisi Fasilitas Sanitasi Dasar Di Sekolah Dasar Kecamatan Baradatu Kabupaten Way Kanan Tahun 2025 - Munawaroh Munawaroh; Suami Indarwati; Karbito Karbito (MIDWIFERY JOURNAL, 2026)
Background: Schools play an important role as an extension of the family in shaping children’s behavior, including health behavior. An unhealthy school environment can disrupt the teaching and learning process; therefore, adequate basic sanitation facilities are needed.Objective: This study aimed to determine the condition of basic sanitation facilities in elementary schools in Baradatu District, Way Kanan Regency, in 2025.Methods: This study used a descriptive design with a population of all elementary schools in Baradatu District, totaling 32 schools. The variables observed included clean water facilities, school toilets, handwashing facilities with soap (HWWS), wastewater management, and solid waste management.Results: The results showed that 21.87% of schools had a distance between the clean water source and septic tank of ≤10 meters, 87% of schools did not have toilets in clean condition, 54% of schools did not have HWWS facilities, and 90.62% of schools did not routinely desludge septic tanks. In addition, 53.12% of schools had not met waste management requirements, such as the unavailability of trash bins in every classroom and canteen.Conclusion: The condition of basic sanitation facilities in elementary schools in Baradatu District had not yet met the required standards. Improvements are needed through the provision of standard clean water facilities, improved toilet cleanliness, provision of HWWS facilities, regular septic tank desludging, and better waste management.Suggestion: Schools need to improve basic sanitation facilities through the provision of standard clean water, improved toilet cleanliness, provision of HWWS facilities, regular septic tank desludging, and better waste management. Related agencies are expected to conduct regular guidance and supervision. Keywords: School sanitation, clean water, toilets, handwashing facilities, waste management. ABSTRAK Latar Belakang: Sekolah merupakan perpanjangan tangan keluarga dalam membentuk perilaku anak, termasuk perilaku kesehatan. Lingkungan sekolah yang tidak sehat dapat mengganggu proses belajar mengajar sehingga diperlukan fasilitas sanitasi dasar yang memadai.Tujuan: Penelitian ini bertujuan untuk mengetahui kondisi fasilitas sanitasi dasar di sekolah dasar Kecamatan Baradatu, Kabupaten Way Kanan Tahun 2025.Metode: Penelitian ini menggunakan desain deskriptif dengan populasi seluruh sekolah dasar di Kecamatan Baradatu sebanyak 32 sekolah. Variabel yang diamati meliputi sarana air bersih, jamban sekolah, sarana cuci tangan pakai sabun (CTPS), pengolahan limbah cair, dan pengelolaan sampah.Hasil: Hasil penelitian menunjukkan bahwa 21,87% sekolah memiliki jarak sumber air bersih dengan tangki septik ≤10 meter, 87% sekolah belum memiliki jamban dalam kondisi bersih, 54% sekolah belum memiliki sarana CTPS, dan 90,62% sekolah belum melakukan penyedotan lumpur tinja secara rutin. Selain itu, 53,12% sekolah belum memenuhi persyaratan pengelolaan sampah, seperti belum tersedianya tempat sampah di setiap kelas dan kantin.Kesimpulan: Disimpulkan bahwa kondisi fasilitas sanitasi dasar di sekolah dasar Kecamatan Baradatu masih belum memenuhi persyaratan sehingga diperlukan perbaikan melalui penyediaan sarana air bersih sesuai standar, peningkatan kebersihan jamban, penyediaan sarana CTPS, penyedotan lumpur tinja secara berkala, serta pengelolaan sampah yang lebih baik.Saran: Sekolah perlu meningkatkan fasilitas sanitasi dasar melalui penyediaan air bersih sesuai standar, perbaikan kebersihan jamban, penyediaan sarana CTPS, penyedotan lumpur tinja secara berkala, serta pengelolaan sampah yang lebih baik. Dinas terkait diharapkan melakukan pembinaan dan pengawasan secara rutin. Kata Kunci: Sanitasi sekolah, air bersih, jamban, CTPS, pengelolaan limbah.